The curse of tolerance and the art of respect in the encounter of knowledges - 1a. Part - Barbosa Neto, Edgar Rodrigues; Goldman, Marcio (Revista de Antropologia, 2022)
Based on an analytical elaboration of the notion of respect, as it is formulated in African American religions and other afroindigenous groups, the article seeks to display the centrality of this notion in the practices linked to these traditions and, from that point onwards, to connect this notion with the practice of anthropology itself. Through a careful juxtaposition between philosophers, writers, indigenous, afroindigenous, Quilombola and Afro-Brazilian thinkers, it speculates about the possibility of a more respectful relationship with other practices of knowledge. A relationship that would be capable of contributing to the renewal of our own practices of knowledge. In this sense, the experience of the so-called “Encontro de Saberes” works as a context from which we set out to think about these issues in order to establish a transversal relationship with the practices with which we seek to dialogue. A relationship defined by the most absolute respect for the frontiers that we have to cross in order to establish this dialogue, as well as by the shame against any possibility of assimilating or destroying that what we intend to establish a relationship with.